2017
DOI: 10.1007/s13280-017-0939-1
|View full text |Cite
|
Sign up to set email alerts
|

Researchers must be aware of their roles at the interface of ecosystem services science and policy

Abstract: Scientists working on ecosystem service (ES) science are engaged in a mission-driven discipline. They can contribute to science-policy interfaces where knowledge is co-produced and used. How scientists engage with the governance arena to mobilise their knowledge remains a matter of personal choice, influenced by individual values. ES science cannot be considered neutral and a discussion of the values that shape it forms an important part of the sustainability dialogue. We propose a simple decision tree to help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 47 publications
1
47
0
2
Order By: Relevance
“…A recent study has shown in particular that researchers can adopt different stances and have different roles in ES research (Crouzat et al 2018). In our action research proposition, the researchers become part of the action arena, where they can play two different roles: they can act as facilitators that propose tools and methods to foster collective learning among stakeholders, or they can act as informants that take part in the collective learning processes and share their knowledge on the SES, for example on the ecological processes underlying key ES.…”
Section: An Actionable Frameworkmentioning
confidence: 99%
“…A recent study has shown in particular that researchers can adopt different stances and have different roles in ES research (Crouzat et al 2018). In our action research proposition, the researchers become part of the action arena, where they can play two different roles: they can act as facilitators that propose tools and methods to foster collective learning among stakeholders, or they can act as informants that take part in the collective learning processes and share their knowledge on the SES, for example on the ecological processes underlying key ES.…”
Section: An Actionable Frameworkmentioning
confidence: 99%
“…Assessments "humble listener" (Pascual et al 2017;Rantala et al 2017): to respect and be open to learning new things across cultures, positions, and values; can take place via engaging stakeholders as coauthors to assessments and as equal advisors in expert groups to enrich global assessments with local and regional knowledge "adaptive expert" (Pullin et al 2016;Rantala et al 2017): to adapt the scope and insights of assessments to issues raised during knowledge coproduction processes; can take place via extended stakeholder review processes, double-sided critique, and expert consultations by focus groups or Delphi panels "officer" (Pullin et al 2016;Crouzat et al 2018): to synthetize and formalize diverse views to robust and legitimate definitions, methods, and interpretations; can take place by structuring diversity, identification of commonalities and differences, and ranking alternatives Capacity building "empathetic visitor" (Rantala et al 2017): to show understanding for stakeholders' concerns and enable their capacity to act; can take place via considering scientists as visitors who can learn from local communities and by supporting horizontal relationship building within and between local communities "trustworthy matchmaker" (Michaels 2009;Rantala et al 2017): to earn trust by providing knowledge and networks; can take place via inclusion of local communities to networks of knowledge by identification of what expertise local communities need, who can provide it, and the best ways to make required connections "conservation supporter" (O'Connell et al 2019): to use best available science to provide support for local institutions for conservation; can take place by enhancing local capacities for environmental monitoring and supporting predetermined capacity-building processes replicated in various sites. Policy support "policy enabler" (Berkes 2007): to enable local communities and institutions to design, implement, and evaluate policies that ease the problems local communities face; can take place via providing resources (e.g., time, expertise, finances, equipment, tools) with flexible opportunities for their use "fair deliberator" (Michaels 2009;Rantala et al 2017): to facilitate interactions and negotiations to address key issues related to codefined policy problems; can take place via workshops and meetings with linkages to policy makers at local and other levels.…”
Section: Work Area Affirmative Roles Collaborative Roles Authoritativmentioning
confidence: 99%
“…"policy advocate" (Michaels 2009;Crouzat et al 2018;Reed et al 2018): to promote knowledge, tools, and methods to be used to push agendas for sustaining ecosystem services; can take place via identification and working with relevant decision makers to ensure policies and governance secure ecosystem services Outreach "(self-)reflexive communicator" (Kunseler & Tuinstra 2017): to reveal hidden motives and agendas affecting outputs and decision making; can take place via transparency on underlying power structures and interests of all involved parties "holistic mediator" (Löfmarck & Lidskog 2017;Rantala et al 2017): to merge western sciences (e.g., natural, social) with local knowledge capturing the plurality of world views to create a holistic view; can take place via sketching alternative solutions and maintaining distinct styles of diverse knowledge systems in outputs "thought leader" (Díaz et al 2018;Reed et al 2018): to consider ecosystem services as the paradigm to understand the central role of culture in defining links between people and nature; can take place via effective dissemination arguing ecosystem services' relevance for various policy settings local people into the 4 IPBES work areas: assessments, capacity building, policy support, and outreach. To achieve our aims, we performed 2 analytical exercises.…”
Section: Work Area Affirmative Roles Collaborative Roles Authoritativmentioning
confidence: 99%
See 1 more Smart Citation
“…In een andere case slaagde de samenwerking niet omdat het project door slechts één persoon werd getrokken en het dus niet voldoende intersectoraal verankerd was. Het vrijmaken van middelen voor een neutrale spilfiguur of honest broker(Crouzat et al, 2018) kan een intersectorale samenwerking aanzienlijk versterken (zie 5.5 Middelen).In de stedelijke context is er over het algemeen weinig formele beleidscontext omtrent GBN, in tegenstelling tot het buitengebied waar programma's en kaders bestaan zoals Natura 2000, Landinrichtingsprojecten van VLM, Integraal waterbeheer… Er zijn echter wel uitzonderingen zoals in de case Groenklimaatassen in Gent (C1) en de Gobelin case-study Landen waar in de stedelijke beleidsplannen expliciet naar GBN wordt verwezen. De ontwikkeling van een GBN wordt in sommige steden aangegrepen om lokale noden te koppelen aan bovenlokale doelstellingen zoals aan strategische projecten, het Sigmaplan, etc.…”
unclassified